2018
DOI: 10.1038/s41598-018-28744-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the oxidation of Cu nanowires and development of an easy to produce, oxidation-resistant transparent conducting electrode using a PEDOT:PSS coating

Abstract: Oxidation can strongly influence the performance of Cu nanowires (CuNWs) by decreasing their conductivity. Here, we identify and investigate a way to prevent the oxidation process of CuNWs to maintain the high conducting performance of CuNWs as transparent electrodes. CuNWs were synthesised using an aqueous method. We prepared several temperature treatments (from 0–300 °C) to represent oxidation of CuNWs in different environments, to study the oxidation process and changes in morphology in detail. Depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…A nanowire-based transparent conductive film has the advantages of excellent photovoltaic performance, low preparation cost, and it could be used to prepare flexible devices. CuNWs are being used to prepare flexible transparent conducting substrates because of their low cost and ease of fabrication on a large area 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…A nanowire-based transparent conductive film has the advantages of excellent photovoltaic performance, low preparation cost, and it could be used to prepare flexible devices. CuNWs are being used to prepare flexible transparent conducting substrates because of their low cost and ease of fabrication on a large area 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 2θ peaks at 36.56°, and 61.45° are the characteristic peaks of the all the composite fabricated in this study. CuFC exhibits 2θ peaks at 36.4°, 52.5°, 64.5°, and 76.8° imply presence of corresponding reflective planes of Cu nanomaterials such as (110), (200), (113), and (220), respectively [ 19 ]. The 2θ peaks of CoFC at 38.3°, and 62.…”
Section: Resultsmentioning
confidence: 99%
“…As multiple researchers have already found that oxidation is the main factor in a resistivity increase in metal/polymer nanocomposites (excluding noble metals) [3,7,8], it has to be minimized to retain the conductive properties of the filament material. Since high temperatures accelerate the oxidation process [36], low nozzle temperatures and increased cooling of the extruding material can reduce the filler oxidation. Further, a low printing speed and extrusion rate reduce the shear rate in the nozzle narrowing and reduce the damage of the established conductive network during the extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation of copper nanowires and other metal nanoparticles was already thoroughly studied [36,37] and practical solutions exist, mostly in the form of coatings with ligand molecules [38] and inert metals [8].…”
Section: Discussionmentioning
confidence: 99%